The Need for Diversification of Forensic Tactical Rules Applicable to Crime Scene Investigation - PALCU, Pavel (Journal of Legal Studies, 2017)
The unprecedented development of cybernetics was concretized by the emergence of computer technology in ways difficult to predict. In this context, the international underworld and organized crime have expanded the area of criminal acts, but equally there were new investigation possibilities for the police and judicial authorities, limiting the role of intuition and flair, of human spontaneity, the center of gravity falling on their ability to use new technology intelligence they have at their disposal.